Governing Blockchain-based Token in Indonesia: Legal and Technical Perspective - Yun Santoso, Wahyu; Anggara Putra, Araya; Hendson Passagi, Jonathan; Rifky Hanindya, Yoda; Azura Tagar, Annisa (Brawijaya Law Journal, 2020)
In the past decade, blockchain technology has caught the world's attention because of its disruptive nature in various industries. Along with blockchain adoption, blockchain-based token, or more popularly known as the "token", are widely used as a representation of a certain asset. In its development, blockchain innovators continue to encourage the birth of new tokens with more diverse attribution. From the regulator's point of view, the above gave rise to problems in the formation of regulations relating to tokens, mainly on its legality whether token will be determined as currency, securites, or commodity. If regulations still cannot catch up with the gap of technological advancement, this will actually hinder the development of blockchain technology in Indonesia.The token regulatory framework has been designed in several countries which have provided clear distinguishing characteristics for each type of token. However, in Indonesia, the absence of a clear and distinct definition of the types of tokens creates legal uncertainty for stakeholders. Therefore, this paper aims to give clarity to the legality of Blockchain-based tokens in Indonesia.